ETHANOL, CORN, AND BROILER: THE INTERDEPENDENCE BETWEEN THE GLOBAL CHAINS - Ferragi, E. M.; Naas, I.A. (Revista Brasileira de Engenharia de Biossistemas, 2015)
This study aimed to assess the impact of the increase in the United States (US) ethanol production from corn, between 2000 and 2012, and extendedly in the broiler production. A comparative production analysis of the three commodities production in the US and Brazil was given in order to understand the effect on their supply chains. Results indicated that the increase in the US ethanol production was not followed by the local corn and broiler production. Reflexes of the increase in US ethanol production were found in Brazilian broiler production since the corn supply was historically dependent of the US supply. We have also found an excellent opportunity for Brazilian corn production increase with a direct result in ethanol and broiler production since further logistics, and infrastructure solutions are given.